Analysis of skin tissues spatial fluorescence distribution by the Monte Carlo simulation - Churmakov, D. Y.; Meglinski, Igor V.; Piletsky, Sergey A.; Greenhalgh, Douglas A. (Institute of Physics (IOP), 2003)
A novel Monte Carlo technique of simulation of spatial fluorescence distribution within the human skin is presented. The computational model of skin takes into account the spatial distribution of fluorophores, which would arise due to the structure of collagen fibres, compared to the epidermis and stratum corneum where the distribution of fluorophores is assumed to be homogeneous. The results of simulation suggest that distribution of auto-fluorescence is significantly suppressed in the near-infrared spectral region, whereas the spatial distribution of fluorescence sources within a sensor layer embedded in the epidermis is localized at an ‘effective’ de